Avaliação da compatibilidade entre Y-TZP e BICUVOX para obtenção de compósitos condutores de íons de oxigênio - Piva, Roger Honorato (2013)
The BICUVOX is a potential candidate for devices that require materials with high ionic conductivity at intermediate temperatures. However, deficiencies such as low mechanical resistance and thermodynamic stability in reducing atmospheres have been introducing unsolved obstacles for technological appliance of this material. Unlike BICUVOX, the Y-TZP phase presents high mechanical resistance and high stability under reducing atmospheres. However, it does not display high ionic conductivity at intermediate temperatures. In this work we studied the compatibility between the BICUVOX and Y-TZP for the development of composites oxygen ion conductors. The composites were prepared by liquid phase and solid-state sintering. All characteristics were determined by XRD, SEM, DSC, diametral compression, impedance spectroscopy and treatments in H2 atmosphere. Using the BICUVOX as liquid phase additive, destabilization of tetragonal zirconia and formation of YVO4 take place. However, the solid state sintering enables the development of dense composite with up to 26% of Y-TZP. The composite with 26% of Y-TZP exhibited α = 10.10-6 ºC-1, which is a lower value than the one found for the BICUVOX, in addition to 144% higher mechanical resistance than for the BICUVOX. Also, for this composite a deleterious order-disorder transformation, γ ↔γ, was inhibited. All these improvements are attributed to the effect of Y-TZP both in the inhibition of grain growth, as well as in the preferential location among the grain boundaries of the BICUVOX matrix. However, the increase of grain boundaries and the Y-TZP as an additional phase, reduced the total electrical conductivity in composites. No resistance to γ-Bi4V1,8Cu0,2O10,7 phase decomposition was observed after exposure to H2. A general assessment indicates that the best properties are found in composite with 13 and 26% of Y-TZP, showing some improved properties in relation to each isolated materials.